Kritik Sosial terhadap Keluarga dalam Iklan Olay Versi Sampai Kapan Lebaran Ditanya 'Kapan'? - Yasmine, Devina Ariga; Agustrijanto, Agustrijanto (UNIVERSITAS KALBIS, 2024)
Life decision-making in the social life of young people at this time is still often managed by the family. Families feel in control of their lives so that they are free to take them over. It is this phenomenon that is raised in the advertisement for the Olay product version of ‘Sampai Kapan Lebaran Ditanya ‘Kapan’?'. Therefore this ad attracts the attention of researchers to examine from the side of how social criticism of the family is displayed in the ad. This study uses Stuart Hall's representation theory. Then the critical paradigm and qualitative approach are also chosen in this study. The data were analyzed using Roland Barthes' semiotics to see how denotations, connotations, and myths were generated in advertisements. The results of the study show that the family carries out a negative function, namely being the perpetrator of judgment and bringing down younger family members.